Malignant Bone Tumors of the Knee: How to Identify and Treat - Voskuil, Ryan; Evenski, Andrea J.; Montgomery, Corey; Emory, Cynthia L. (The Journal of Knee Surgery, 2019)
Malignant bone tumors are rare conditions that may be encountered by nononcologic surgeons only a few times in their careers, but a delay in diagnosis or a misinterpretation of data can have limb and life-threatening consequences. Prior literature suggests that unplanned resection of sarcoma was associated with an increased risk of local recurrence, decreased 10-year survival, and increased amputation rate compared with planned resection. In addition to patient morbidity, missed diagnoses and unplanned excisions of malignant tumors lead to increased cost of treatment and higher likelihood of subsequent medicolegal action. According to the American Cancer Society, the 5-year survival of all combined cases of malignant bone tumors is approximately 70%. However, the survival rate of each type of malignant bone tumor varies, with multiple myeloma survival rates being much lower and lymphoma somewhat higher. These rates depend on many factors including grade, stage, and chemotherapy response. For example, the 10-year survival of localized osteosarcoma is almost 70%, yet rapidly declines to 20 to 30% in patients with metastases. This further emphasizes the elevated importance of prompt recognition and treatment of malignant bone tumors.
Keywords: malignant bone tumors; osteosarcoma; lymphoma; chondrosarcoma